Effects of Mexiletine and Lacosamide on Nerve Excitability in Healthy Subjects: A Randomized, Double‐Blind, Placebo‐Controlled, Crossover Study. Issue 5 (19th July 2022) - Ruijs, Titia Q.; Koopmans, Ingrid W.; de Kam, Marieke L.; van Esdonk, Michiel J.; Koltzenburg, Martin; Groeneveld, Geert Jan; Heuberger, Jules A.A.C.
Abstract : Selective voltage‐gated sodium channel blockers are of growing interest as treatment for pain. For drug development of such compounds, it would be critical to have a biomarker that can be used for proof‐of‐mechanism. We aimed to evaluate whether drug‐induced changes in sodium conductance can be detected in the peripheral nerve excitability profile in 18 healthy subjects. In a randomized, double‐blind, 3‐way crossover study, effects of single oral doses of 333 mg mexiletine and 300 mg lacosamide were compared with placebo. On each study visit, motor and sensory nerve excitability measurements of the median nerve were performed (predose; and 3 and 6 hours postdose) using Qtrac. Treatment effects were calculated using an analysis of covariance (ANCOVA) with baseline as covariate. Mexiletine and lacosamide had significant effects on multiple motor and sensory nerve excitability variables. Depolarizing threshold electrotonus (TEd40 (40–60 ms)) decreased by mexiletine (estimated difference (ED) −1.37% (95% confidence interval (CI): −2.20, −0.547; P  = 0.002) and lacosamide (ED −1.27%, 95% CI: −2.10, −0.443; P  = 0.004) in motor nerves. Moreover, mexiletine and lacosamide decreased superexcitability (less negative) in motor nerves (ED 1.74%, 95% CI: 0.615, 2.87; P  = 0.004, and ED 1.47%, 95% CI: 0.341, 2.60; P  = 0.013, respectively). Strength‐duration time constant decreased after lacosamide in motor‐ (ED −0.0342 ms, 95% CI: −0.0571, −0.0112; P  = 0.005) and sensory nerves (ED −0.0778 ms, 95% CI: −0.116, −0.0399; P  < 0.001). Mexiletine and lacosamide significantly decrease excitability of motor and sensory nerves, in line with their suggested mechanism of action. Results of this study indicate that nerve excitability threshold tracking can be an effective pharmacodynamic biomarker. The method could be a valuable tool in clinical drug development.